Mapeamento Eletroanatômico Endocárdico e Epicárdico associado à Tomografia de Coração em pacientes com Cardiopatia Chagásica Crônica e Taquicardia Ventricular Sustentada - Valdigem, Bruno Pereira [UNIFESP] (2011)
BACKGROUND: Chronic Chagasic Cardiomiopathy (CCC) is a parasitic disease where epicardial VTs are common. Eletroanatomic mapping merged with CT scan data is a useful tool for mapping the endocardium, and its accuracy in guiding ablation on the epicardium was not adequately evaluated . OBJECTIVE: Compare electronatomic map merged with Heart CT to fluoroscopy for epicardial ablation of CCC. Describe the distribution of the scars on CCC. METHODS AND RESULTS: We performed epicardial and endocardial mapping and ablation using electroanatomic mapping on eight patients and merged the map with coronary arteries CT Scan using at least three landmarks. To compare the 3D image obtained with 3dEA mapping with image integration capabilities and the 2D fluoroscopic image obtained during the ablation procedure we used vectorial computer graphic software in order to prove the images were equivalent and to compare the distance between the catheter tip on fluoroscopy to catheter tip on 3D EA map. EPRFCA was successfully performed in all patients and they did not present recurrence for at least 3 months follow up. The mean difference between the tip of the catheter on fluoroscopy and on the 3D model was 6.03 ± 2.09mm. Scars were present in the epicardium and endocardium and most of patients presented with posterior wall scars and RV scar. CONCLUSION: The combination of electroanatomic map and heart CT scan data is feasible and can be an important tool for EPRFCA in patients with CCC and VT.